Impact of injection buffer volume to perform bronchoalveolar lavage fluid collection for isolating alveolar macrophages to investigate fine particle-induced IL-1α secretion. Issue 1 (1st January 2021) - Sasaki, Eita; Momose, Haruka; Furuhata, Keiko; Mizukami, Takuo; Hamaguchi, Isao
Abstract: The importance of alveolar macrophages has been reported in many toxicology/immunology studies. Alveolar macrophages release interleukin (IL)-1α as a damage-associated molecular pattern (DAMP) when stimulated by fine particles. However, it is unclear whether cell isolation procedures affect ex vivo particle-induced responses in primary mouse alveolar macrophages (mAM). In this study, effects of injection buffer volume used to perform bronchoalveolar lavage fluid (BALF) collection to isolate mAM for use in ex vivo particle-induced responses were assessed. Among the mAM obtained from BALF collected using a 0.55 or 0.75 ml, but not a 1.0 ml buffer injection volume, decreased cell viability and IL-1α release were observed when cells were stimulated ex vivo with silica crystal or aluminum salt. Injected buffer composition did not affect the IL-1α release. On the other hand, IL-6 secretion induced by lipopolysaccharide (LPS) did not differ among mAM obtained from BALF collected using the different volumes. Expression levels of cell surface markers like CD11c, SiglecF, and CD64 did not differ among mAM obtained from BALF collected using the different injection buffer volumes. IL-1α release (and also necroptosis) induced by ex vivo particle stimulation was suppressed by RIPK3 inhibitor or cytochalasin D co-treatment. Decreases in RIPK3 phosphorylation were noted in mAM obtained in BALF collected using the 1.0 ml injection volume compared with mAM obtained in BALF using 0.55 or 0.75 ml buffer. These observations illustrate that larger volumes of buffer used to collect BALF from mice can affect sensitivity of the isolated mAM to ex vivo particle-induced responses by inhibiting their functions.